Penentuan Struktur Urat Kuarsa (Vein) Berdasarkan Respon Geolistrik Resistivity pada Lokasi X Kabupaten Ketapang Kalimantan Barat - Firman (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2018)
Geoelectric resistivity method is a geophysical method commonly used in the interpretation of the subsurface by injecting an electric current down the surface to obtain information about the distribution of the value of resistivity of the rock. This study aims to identify the structure of a quartz vein (vein) which is thought to contain gold mineral at the location x. Measurements carried out as many as three tracks with electrodes spaced 5 meters, each 75 meters long, and the penetration depth of 15 meters from surface. Results obtained from the data processing is done with a software tool Res2dinv the form of a cross section 2D resistivity. From the data processing is seen that possible zonasilification as quartz vein (vein) and is thought to contain gold mineral found at an elevation of 602-610 meters . While the 3D model of the interpolated trajectory I and II shown that uric guess shaped Massive Vein.